Finite element modeling of synthetic fiber-ropes - Akalp, Umut. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
The synthetic fiber ropes are used in many fields such as cord fabrics, industrial fabrics, power transmission systems, tires and off-shore applications. The ropes are formed by twisting a small number of yarns which are produced as monofilaments or multi-filaments put together and twisted. Although the use of fiber ropes spread to many fields, there are various challenges related to the characterization and modeling of their mechanical behavior. The main difficulties are associated with the complicated rope structure, the characteristics of the fiber material, contact modeling and determination of friction properties. Modeling of rope is important because a realistic model would allow the manufacturer as well as the user to be more efficient in designing their products and would reduce the amount of laboratory experiments. In the study a computational model for twisted yarns and ropes that are composed of many synthetic fibers is developed. In particular two-yarn rope with linear elastic-linear strain hardening material behavior is modeled. The effect of various parameters on mechanical behavior of the rope is investigated through the computational model. Various contact models are investigated and effects of friction, twist level, and initial twist on the axial response of the rope, stress distribution and contact stresses are studied. Results are compared with the results available in the literature.
Keywords: Rope.; Textile fibers, Synthetic.